Aramid membrane, method of manufacture and apparatus
Patent Information
- Application Number
- CN202211278132.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-19
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-10-19
AI Technical Summary
目前间位芳纶材料用于隔膜主要通过静电纺丝法制备,如中国专利技术201910686373.1、201811529222.7、201810835751.3等,但是静电纺丝法自身的一些限制,比如效率低,价格高,隔膜强度较低,不适合于大规模应用
[0028](1)芳纶聚合物分散液通过模头挤出到经预热辊加热的钢带上,并经过干燥箱促进溶剂挥发,然后快速转移到冷却辊,并经过低温箱进一步降温,在温度骤降过程中,分子链快速收缩,致使芳纶聚合物分子链距离增加,从而产生初始的微小缺陷,为后续双向拉伸造孔提供基础。水洗过程中伴随着超声处理,进一步在双向拉伸机上进行纵横向牵伸后,得到理想的孔隙结构,通过在高温箱中进行热定型,最终制备长期在高温环境下工作的高安全性芳纶隔膜。
Smart Images

Figure CN115548579B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials, and specifically relates to an aramid diaphragm, its preparation method, and apparatus. Background Technology
[0002] In various chemical power sources, the separator material plays a crucial role in blocking positive and negative electrode reactions, preventing electrons from passing through, and allowing ions to pass through the internal circuitry. In recent years, lithium-ion batteries have been widely used in mobile power supplies, electric vehicles, and other fields, with their energy density continuously improving to meet the demand for extended battery life. However, this has also led to numerous safety issues such as spontaneous combustion or explosions of lithium-ion batteries. The separator is a vital component of a lithium-ion battery. Good chemical stability and mechanical strength of the separator ensure the integrity of the lithium-ion battery during use, preventing short circuits or even spontaneous combustion caused by contact between the positive and negative electrodes. Due to the inherent properties of the substrate, PE ceramic separators shrink and deform severely at temperatures above 150°C, easily leading to internal short circuits and thermal runaway. Therefore, the development of high-strength, high-performance, and high-safety lithium-ion battery separators has become a current research hotspot. Developing high-performance separators that can replace polyolefin separators is of great significance for improving the performance of lithium-ion batteries.
[0003] Aramid, as a high-temperature resistant specialty polymer material, is widely used in industry. It possesses extremely high thermal stability (up to 400℃), excellent self-extinguishing properties, and good wettability to electrolytes, making it a promising candidate material for high-performance membranes. Currently, meta-aramid materials for membranes are mainly prepared via electrospinning, as illustrated in Chinese patents 201910686373.1, 201811529222.7, and 201810835751.3. However, electrospinning itself has limitations, such as low efficiency, high cost, and relatively low membrane strength, making it unsuitable for large-scale applications. Some researchers have also used high-temperature resistant materials such as aramid to coat the surface of polyolefin substrates to improve their temperature resistance, as illustrated in Chinese patents 201821819348.3, 202110431425.8, and 202210268442.9. However, these methods undoubtedly increase manufacturing costs and process complexity. Some researchers have also prepared aramid separators by wet stretching and extraction or curing aramid polymers or by adding functionally modified fillers, such as 202010339804.X, 201810782506.0, and 202210174186.7. While these separators exhibit high performance, their yield rate is limited. Therefore, there is an urgent need to develop a technology for aramid separators used in batteries that is suitable for large-scale production. Summary of the Invention
[0004] The primary objective of this invention is to overcome the shortcomings and deficiencies of the prior art and provide an aramid separator for battery separators.
[0005] Another object of the present invention is to provide an aramid membrane prepared by the method described above.
[0006] Another object of the present invention is to provide the application of the aramid separator for lithium batteries.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A film-forming apparatus includes: an extrusion die, a preheating roller, a cooling roller, a drying roller, a take-up roller, a drying chamber, a low-temperature chamber, and a washing tank. The preheating roller and the cooling roller are surrounded by a steel strip, which runs on the surface of the preheating roller and the cooling roller. The film-forming liquid is transferred to the surface of the steel strip through the extrusion die, enters the drying chamber with the movement of the steel strip, then enters the low-temperature chamber directly through the cooling roller, and then passes through the washing tank and the drying roller in sequence, and is wound up by the take-up roller.
[0009] Preferably, the drying chamber is equipped with an air extraction port, and the low-temperature chamber is equipped with a cold air inlet.
[0010] A method for preparing an aramid separator includes the following steps:
[0011] (1) Preparation of aramid polymer solution;
[0012] (2) The aramid polymer dispersion is obtained by diluting the aramid polymer solution, and then the aramid membrane is prepared by the film forming device;
[0013] (3) The obtained aramid membrane is subjected to biaxial stretching and further heat setting to finally obtain an aramid diaphragm.
[0014] Preferably, the steps for preparing the aramid film in step (2) are as follows: the aramid polymer dispersion is extruded through an extrusion die onto a steel strip heated by a preheating roller, the solvent is evaporated in a drying oven, and then the strip is rapidly cooled by a cooling roller and a low-temperature chamber. The strip is then thoroughly washed in a water washing tank, accompanied by ultrasonic treatment. After being thoroughly dried on the surface of the drying roller, the strip is wound up by a winding roller. The extrusion speed is 0.1 to 10 m / min, and the linear velocity of the steel strip surface is 0.1 to 60 m / min.
[0015] Preferably, the extrusion speed is 0.5 to 5.0 m / min; the surface linear velocity of the steel strip is 1.0 to 50 m / min.
[0016] Preferably, in step (2), the surface temperature of the preheating roller is 60-200℃, the surface linear velocity of the preheating roller is 0.1-50m / min; the temperature of the cooling roller is 5-50℃, the surface linear velocity of the cooling roller is 0.1-50m / min; and the average temperature inside the cooling box is 5-40℃.
[0017] Preferably, in step (2), the surface temperature of the preheating roller is 70-140℃, and the surface linear velocity of the preheating roller is 1-10m / min; the temperature of the cooling roller is 20-40℃, and the surface linear velocity of the cooling roller is 1-10m / min; the surface temperature of the drying roller is 60-200℃, and the average temperature inside the drying chamber is 60-200℃; the ultrasonic treatment has a power of 200-1500W, a temperature of 20-90℃, and a time of 5-60min.
[0018] Preferably, the extrusion die parameters in step (2) are a die length of 200±50mm and a width of 20-500μm.
[0019] Preferably, in step (1), the preparation of the aramid polymer solution is as follows: a neutral aramid polymer solution is prepared by polymerizing m-phenylenediamine and isophthaloyl chloride in an organic solvent under low temperature and protective atmosphere conditions; the molar ratio of m-phenylenediamine to isophthaloyl chloride is 100:(85-120); and isophthaloyl chloride is added in 2-5 batches.
[0020] Preferably, the concentration of the aramid polymer dispersion in step (2) is 5-30% by mass, more preferably 10-25%; the aramid polymer dispersion is also subjected to vacuum defoaming pretreatment.
[0021] Preferably, the bidirectional stretching in step (3) specifically involves a transverse stretching of 1.3-5.0 times and a longitudinal stretching of 1.3-5.0 times; the heat setting temperature is 280-330℃, and the time is 1-30 min.
[0022] Preferably, in step (1) the preparation of the aramid polymer: under low temperature and nitrogen protection atmosphere, the cosolvent and m-phenylenediamine are dissolved in N,N-dimethylacetamide, and then isophthaloyl chloride is added to obtain a reaction solution; as the reaction proceeds, the temperature of the reaction solution gradually increases, and after heat preservation treatment, an alkaline agent is added for neutralization to prepare a neutral aramid polymer solution; the molar ratio of m-phenylenediamine to isophthaloyl chloride is 100:(85-110).
[0023] Preferably, the co-solvent is one or more of lithium bromide, lithium chloride, calcium chloride, and calcium bromide; the heat preservation treatment is performed at 40-80°C for 0.5-12 hours; and the alkaline agent is one or more of calcium oxide, calcium hydroxide, lithium hydroxide, magnesium hydroxide, sodium hydroxide, and organic amines.
[0024] Preferably, the bidirectional stretching in step (3) specifically involves a transverse stretching of 2.0-5.0 times and a longitudinal stretching of 2.0-5.0 times; the heat setting temperature is 290-330℃, and the time is 1-20 min.
[0025] The aramid membrane can be used in the preparation of lithium batteries, lithium-sulfur batteries, electrical insulation materials, adsorption and filtration materials, and flexible electronic device substrates.
[0026] The method and apparatus for preparing aramid membranes described above are also applicable to membrane formation from other raw materials, such as para-aramid, polyacrylonitrile, viscose, spandex and other synthetic fiber polymers.
[0027] The present invention has the following advantages and effects compared with the prior art:
[0028] (1) The aramid polymer dispersion is extruded through a die onto a steel strip heated by a preheating roller. After passing through a drying oven to promote solvent evaporation, it is rapidly transferred to a cooling roller and further cooled in a low-temperature oven. During this rapid temperature drop, the molecular chains contract quickly, increasing the distance between the aramid polymer molecular chains and creating initial micro-defects, thus providing a basis for subsequent biaxial stretching and pore formation. The washing process is accompanied by ultrasonic treatment. Further longitudinal and transverse stretching on a biaxial stretching machine yields an ideal pore structure. Heat setting in a high-temperature oven ultimately produces a high-safety aramid membrane that can operate in high-temperature environments for extended periods.
[0029] (2) After longitudinal and transverse stretching, further heat setting eliminates residual stress, causing the molecular chains or crystals to arrange themselves in an orderly manner along the planar direction. The orientation structure of the macromolecules is fixed under tension or relaxation, and the fiber interface is also tightly bonded under tension. This overcomes the technical difficulties of brittle and easily broken membranes produced by conventional methods, further improving the mechanical strength and pore structure of the diaphragm. This technical solution is convenient and simple to operate, suitable for industrial-scale production, and further expands the industrialization process and application scope of aramid diaphragms.
[0030] (3) The efficient preparation technology of aramid membrane of the present invention can also increase its functionalization and performance by adding functional units (such as functional nanoparticles, conductive polymers, thermally conductive fillers, etc.) to aramid polymers. This is of great significance for the diversified application of aramid membranes in various fields such as battery membranes, reinforcing materials, textile materials, electrically insulating nanopaper, flexible electronic devices, and adsorption filter media. Attached Figure Description
[0031] Figure 1 This is a flowchart illustrating the preparation process of the aramid separator for lithium-ion batteries according to the present invention.
[0032] Figure 2 This is a schematic diagram of the film-forming apparatus for the aramid separator used in lithium battery separators according to the present invention.
[0033] Figure 3 This is a surface electron microscope image of the aramid membrane prepared in Example 4.
[0034] Figure 4 This is a surface electron microscope image of the aramid membrane prepared in Example 5. Detailed Implementation
[0035] The present invention will be further described in detail below with reference to embodiments, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field. Test methods in the following embodiments that do not specify specific experimental conditions are generally performed under conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention are all commercially available.
[0036] The starting materials used in the preparation method of this invention can be purchased from the market or prepared according to existing technical methods.
[0037] like Figure 2 As shown, the forming apparatus for realizing the preparation method of the aramid separator in this embodiment includes: an extrusion die 1; a preheating roller 2; a cooling roller 3; first guide rollers to fourteenth guide rollers 4-17; first drying rollers to fourth drying rollers 18-21; a winding roller 22; an air extraction port 23; a drying box 24; a cold air inlet 25; a low temperature box 26; a steel strip 27; and a water washing tank 28.
[0038] Example 1
[0039] An aramid separator and its preparation method, comprising the following steps:
[0040] (1) Preparation of aramid polymer: Under nitrogen protection at 15°C, an appropriate amount of co-solvent lithium bromide and m-phenylenediamine were dissolved in N,N-dimethylacetamide, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride was 100:85; then isophthaloyl chloride was added in one batch to obtain a reaction solution; as the reaction proceeded, the reaction solution was kept at 50°C for 12 h, and after the heat treatment, calcium oxide was added for neutralization to prepare a neutral aramid polymer solution.
[0041] (2) Preparation of aramid membrane: The aramid polymer dispersion obtained in step (1) is diluted to a suitable concentration and then degassed under vacuum. It is then extruded onto a steel strip 27 through an extrusion die 1. The steel strip is wrapped around the preheating roller 2 and the cooling roller 3. As the steel strip moves, it enters the drying oven 24 to evaporate the solvent. Then, it passes through the cooling roller 3 and directly enters the low-temperature oven 26. After passing through the water washing tank 28, it is thoroughly washed with ultrasonic treatment during the water washing process. After being thoroughly dried on the surfaces of the first to fourth drying rollers 18-21, it is wound up by the take-up roller 22. Subsequently, the obtained aramid membrane is stretched longitudinally and transversely on a biaxial stretching machine and then heat-set in a high-temperature oven to finally prepare a high-performance aramid membrane.
[0042] The concentration of the aramid polymer dispersion is 5% by mass; the extrusion die is 200mm long and 20μm wide, and the extrusion speed is 0.1m / min; the temperature of the preheating roller 2 is 60℃, the surface linear velocity of the steel strip is 0.1m / min, the average temperature inside the drying chamber is 60℃, the surface temperature of the cooling roller 3 is 5℃, and the average temperature inside the cooling chamber is 5℃; the water used for washing is ultrapure water at a temperature of 20℃, the ultrasonic power during the process is 200W, and the time is 60min; the surface temperature of the first to fourth drying rollers 18-21 is 100℃; the biaxial stretching specifically involves a longitudinal stretch (along the direction of diaphragm movement) of 1.3 times and a transverse stretch (perpendicular to the direction of diaphragm movement) of 1.1 times; the heat setting temperature is 280℃, and the time is 30min.
[0043] Example 2
[0044] An aramid separator and its preparation method, comprising the following steps:
[0045] (1) Preparation of aramid polymer: Under nitrogen protection at 10°C, an appropriate amount of cosolvent lithium chloride and m-phenylenediamine were dissolved in N,N-dimethylacetamide, wherein the molar ratio of m-phenylenediamine to isophthaloyl chloride was 100:115; then isophthaloyl chloride was added in two portions to obtain a reaction solution; as the reaction proceeded, the reaction solution was kept at 60°C for 8 hours, and after the heat treatment, calcium hydroxide was added for neutralization to prepare a neutral aramid polymer solution.
[0046] (2) Preparation of aramid membrane: Refer to Example 1.
[0047] The concentration of the aramid polymer dispersion is 12% by mass; the extrusion die is 200mm long and 90μm wide, and the extrusion speed is 0.5m / min; the temperature of the preheating roller 2 is 80℃, the surface linear velocity of the steel strip is 1.1m / min, the average temperature in the drying oven is 100℃, and cooling is performed. The surface temperature of the cooling roller 3 is 20℃, and the average temperature in the cooling oven is 10℃; the water used for washing is ultrapure water at 40℃, the ultrasonic power is 500W, and the time is 30min; the surface temperature of the first to fourth drying rollers 18-21 is 60℃; the biaxial stretching specifically involves longitudinal (along the diaphragm's forward direction) stretching of 1.7 times and transverse (perpendicular to the diaphragm's forward direction) stretching of 1.3 times; the heat setting temperature is 295℃, and the time is 20min.
[0048] Example 3
[0049] An aramid separator and its preparation method, comprising the following steps:
[0050] (1) Preparation of aramid polymer: Lithium chloride and m-phenylenediamine were dissolved in N,N-dimethylacetamide under nitrogen protection at 5°C, with a molar ratio of m-phenylenediamine to isophthaloyl chloride of 100:104; then isophthaloyl chloride was added in three portions to obtain a reaction solution; as the reaction proceeded, the reaction solution was kept at 80°C for 4 hours, and after the heat treatment, calcium oxide was added for neutralization to prepare a neutral aramid polymer solution.
[0051] (2) Preparation of aramid membrane: Refer to Example 1.
[0052] The concentration of the aramid polymer dispersion is 20% by mass; the extrusion die is 200mm long and 500μm wide, and the extrusion speed is 5m / min; the temperature of the preheating roller 2 is 100℃, the surface linear velocity of the steel strip is 50m / min, and the average temperature inside the drying oven is 140℃. The surface temperature of the cooling roller 3 is 50℃, and the average temperature inside the cooling oven is 40℃; the water used for washing is ultrapure water at 60℃, the ultrasonic power is 1000W, and the time is 5min; the surface temperature of the first to fourth drying rollers 18-21 is 150℃; the biaxial stretching specifically involves a longitudinal stretch (along the diaphragm's forward direction) of 2.4 times and a transverse stretch (perpendicular to the diaphragm's forward direction) of 2.2 times; the heat setting temperature is 300℃, and the time is 10min.
[0053] Example 4
[0054] An aramid separator and its preparation method, comprising the following steps:
[0055] (1) Preparation of aramid polymer: Lithium chloride and m-phenylenediamine were dissolved in N,N-dimethylacetamide under nitrogen protection at 8°C, with a molar ratio of m-phenylenediamine to isophthaloyl chloride of 100:120; then isophthaloyl chloride was added in 5 portions to obtain a reaction solution; as the reaction proceeded, the reaction solution was kept at 70°C for 8 hours, and after the heat treatment, calcium hydroxide was added for neutralization to prepare a neutral aramid polymer solution.
[0056] (2) Preparation of aramid membrane: Refer to Example 1.
[0057] The concentration of the aramid polymer dispersion is 28% by mass; the extrusion die is 200mm long and 400μm wide, and the extrusion speed is 5m / min; the temperature of the preheating roller 2 is 110℃, the surface linear velocity of the steel strip is 30m / min, and the average temperature inside the drying chamber is 110℃. The surface temperature of the cooling roller 3 is 50℃, and the average temperature inside the cooling chamber is 20℃; the water used for washing is ultrapure water at 30℃, the ultrasonic power is 1500W, and the time is 10min; the surface temperature of the first to fourth drying rollers 18-21 is 140℃; the biaxial stretching specifically involves a longitudinal stretch (along the diaphragm's forward direction) of 3.3 times and a transverse stretch (perpendicular to the diaphragm's forward direction) of 3.0 times; the heat setting temperature is 320℃, and the time is 1min.
[0058] Example 5
[0059] An aramid separator and its preparation method, comprising the following steps:
[0060] (1) Preparation of aramid polymer: Lithium chloride and m-phenylenediamine were dissolved in N,N-dimethylacetamide under nitrogen protection at 7°C, with a molar ratio of m-phenylenediamine to isophthaloyl chloride of 100:102; then isophthaloyl chloride was added in two portions to obtain a reaction solution; as the reaction proceeded, the reaction solution was kept at 60°C for 5 hours, and after the heat treatment, calcium oxide was added for neutralization to prepare a neutral aramid polymer solution.
[0061] (2) Preparation of aramid membrane: Refer to Example 1.
[0062] The concentration of the aramid polymer dispersion is 18% by mass; the extrusion die is 200mm long and 500μm wide, and the extrusion speed is 2m / min; the temperature of the preheating roller 2 is 100℃, the surface linear velocity of the steel strip is 15m / min, and the average temperature inside the drying chamber is 105℃. The surface temperature of the cooling roller 3 is 30℃, and the average temperature inside the cooling chamber is 15℃; the water used for washing is ultrapure water at 30℃, the ultrasonic power is 1000W, and the time is 20min; the surface temperature of the first to fourth drying rollers 18-21 is 110℃, and the biaxial stretching specifically involves a longitudinal stretch (along the direction of diaphragm movement) of 5 times and a transverse stretch (perpendicular to the direction of diaphragm movement) of 5 times; the heat setting temperature is 290℃, and the time is 10min.
[0063] Compare with Example 1
[0064] The aramid polymer dispersion obtained in step (2) of Example 3 was used to prepare a film by electrospinning, and then various indicators were tested. The results are listed in Table 1.
[0065] The performance testing reference standards for the aramid separator involved in the embodiments of the present invention are as follows, and the test results are listed in Table 1.
[0066] Test methods: Thickness is specified according to GB / T 20628.2-2006; tensile strength and elongation at break are tested according to GB / T29627.2-2013 using the strip specimen method; moisture content is determined according to GB / T29627.2-2013; for heat shrinkage rate, the diaphragm is treated at 200℃ for 1 hour, and the percentage change in area after shrinkage is recorded by photographing and recording the result. The formula is: (A0-A) / A0×100, where A... o This refers to the initial area of the diaphragm, where A is the final area of the diaphragm after heat treatment. The liquid absorption rate is determined as follows: a circular diaphragm with a diameter of 18 mm is immersed in lithium hexafluorophosphide electrolyte for 4 hours, and the mass after immersion is measured. Liquid absorption rate = [(M1-M0) / M0]×100; where M0 and M1 are the masses of the diaphragm before and after immersion in the electrolyte, in grams; puncture resistance is determined according to ASTM F1306-90; porosity is tested using the n-butanol absorption method: a circular diaphragm with a diameter of 18 mm is immersed in n-butanol solution for 4 hours, and the mass after immersion is measured. The porosity is calculated using the formula: porosity = [(M1-M0) / ρV]×100, where M0 and M1 are the masses of the diaphragm before and after immersion in n-butanol, in grams; ρ is the density of n-butanol, 0.81 g / cm³. 3 V represents the volume of the diaphragm, in cm³. 3 Ion conductivity was calculated by measuring the bulk impedance of the simulated battery. Ion conductivity = L / (R×A), where L is the thickness of the separator; A is the effective contact area of the separator; and R is the bulk resistance of the separator (Ω). Battery assembly: In an argon-filled glove box, button batteries were assembled in the following order: positive electrode shell / stainless steel sheet / separator / stainless steel sheet / negative electrode shell. After sealing, the batteries were left to stand for 12 hours before testing. Battery cycle performance was tested by constant current charging and discharging at a current density of 0.5C for 100 cycles, with a voltage range of 3.0V to 4.2V. The capacity retention rate (%) was calculated by dividing the capacity after 100 cycles by the capacity of the first test.
[0067] Table 1. Test data of aramid separators for battery separators prepared in the examples.
[0068]
[0069] As shown in Table 1, the main performance indicators of the high-performance aramid separator described in this invention are superior to those of lithium battery separators prepared by electrospinning. The aramid separator prepared by this invention exhibits excellent puncture resistance, effectively preventing short circuits caused by separator punctures. Furthermore, improving the puncture resistance of the separator helps reduce the deformation of the separator pores, thus promoting the lithium... + The smooth flow of the material. Temperature resistance performance showed that the prepared separator exhibited a shrinkage rate of less than 1% after treatment at 200℃ for 1 hour, ensuring the safety of lithium batteries. Figure 3 and Figure 4 It is known that the aramid separator used in this invention has a uniform pore size and an average pore size of less than 1 μm, which effectively allows ions to pass through while having good ionic conductivity. This enables the aramid separator of this invention to effectively unify the temperature resistance and mechanical properties of battery separator materials, ensuring the safe use of high-performance lithium batteries.
[0070] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A film-forming apparatus for an aramid diaphragm, characterized in that, The device includes: an extrusion die, a preheating roller, a cooling roller, a drying roller, a winding roller, a drying chamber, a low-temperature chamber, and a washing tank. The preheating roller and the cooling roller are surrounded by a steel strip, which runs on the surface of the preheating roller and the cooling roller. The film-forming liquid is transferred to the surface of the steel strip through the extrusion die, enters the drying chamber with the movement of the steel strip, then passes through the cooling roller and directly enters the low-temperature chamber, and then passes through the washing tank and the drying roller in sequence, and is wound up by the winding roller. The film-forming liquid is an aramid polymer dispersion.
2. The film-forming apparatus according to claim 1, characterized in that, The drying chamber is equipped with an air extraction port, and the low-temperature chamber is equipped with a cold air inlet.
3. A method for preparing an aramid separator, characterized in that, Includes the following steps: (1) Preparation of aramid polymer solution; (2) An aramid polymer dispersion is obtained by diluting the aramid polymer solution, and then an aramid membrane is prepared using the film-forming apparatus described in claim 1 or 2; (3) The obtained aramid membrane is subjected to biaxial stretching and then further heat-set to finally obtain an aramid diaphragm.
4. The preparation method according to claim 3, characterized in that, The steps for preparing the aramid film in step (2) are as follows: The aramid polymer dispersion is extruded through an extrusion die onto a steel strip heated by a preheating roller. The solvent evaporates in a drying oven, and the strip is then rapidly cooled by a cooling roller and a low-temperature chamber. It is then thoroughly washed in a washing tank, accompanied by ultrasonic treatment. After being thoroughly dried on the surface by a drying roller, it is wound up by a winding roller. The extrusion speed is 0.1–10 m / min, and the linear velocity of the steel strip surface is 0.1–60 m / min.
5. The preparation method according to claim 4, characterized in that, The extrusion speed in step (2) is 0.1 to 5.0 m / min; the surface linear velocity of the steel strip is 1.0 to 50 m / min.
6. The preparation method according to claim 5, characterized in that, In step (2), the surface temperature of the preheating roller is 60-200℃, and the surface linear velocity of the preheating roller is 0.1-50 m / min; the temperature of the cooling roller is 5-50℃, and the surface linear velocity of the cooling roller is 0.1-50 m / min; the average temperature inside the low-temperature chamber is 5-40℃.
7. The preparation method according to claim 6, characterized in that, In step (2), the surface temperature of the preheating roller is 70-140℃, and the surface linear velocity of the preheating roller is 1-10 m / min; the temperature of the cooling roller is 20-40℃, and the surface linear velocity of the cooling roller is 1-10 m / min; the surface temperature of the drying roller is 60-200℃, and the average temperature inside the drying chamber is 60-200℃; the ultrasonic treatment has a power of 200-1500W, a temperature of 20-90℃, and a time of 5-60min.
8. The method according to any one of claims 4 to 7, characterized in that, Step (1) Preparation of aramid polymer solution: A neutral aramid polymer solution is prepared by polymerizing m-phenylenediamine and isophthaloyl chloride in an organic solvent at low temperature and under a protective atmosphere; the molar ratio of m-phenylenediamine to isophthaloyl chloride is 100:(85-120); isophthaloyl chloride is added in 2-5 batches; The concentration of the aramid polymer dispersion in step (2) is 5-30% by mass, and the aramid polymer dispersion is also subjected to vacuum defoaming pretreatment. The bidirectional stretching in step (3) specifically refers to a transverse stretching of 1.3-5.0 times and a longitudinal stretching of 1.3-5.0 times; the heat setting temperature is 280-330℃ and the time is 1-30min.
9. The method according to claim 8, characterized in that, Step (1) Preparation of aramid polymer: Under low temperature and nitrogen protection atmosphere, the cosolvent and m-phenylenediamine are dissolved in N,N-dimethylacetamide, and then isophthaloyl chloride is added to obtain a reaction solution; as the reaction proceeds, the temperature of the reaction solution gradually increases, and after heat preservation treatment, an alkaline agent is added for neutralization to prepare a neutral aramid polymer solution; the molar ratio of m-phenylenediamine to isophthaloyl chloride is 100:(85~110); The co-solvent is one or more of lithium bromide, lithium chloride, calcium chloride, and calcium bromide; the heat preservation treatment is performed at 40–80°C for 0.5–12 hours; the alkaline agent is one or more of calcium oxide, calcium hydroxide, lithium hydroxide, magnesium hydroxide, sodium hydroxide, and organic amines. The concentration of the aramid polymer dispersion in step (2) is 10-25% by mass; the extrusion die parameters are a die length of 200±50mm and a width of 20-500µm. The bidirectional stretching in step (3) specifically refers to a transverse stretching of 2.0-5.0 times and a longitudinal stretching of 2.0-5.0 times; the heat setting temperature is 290-330℃ and the time is 1-20min.
10. The aramid separator prepared by the method according to any one of claims 3 to 9.
Citation Information
Patent Citations
A preparation method of aramid lithium battery composite separator
CN109004155A
Aramid coating solution, lithium-ion battery separator and its preparation method
CN109181522B
Method for producing ultrafine fiber diaphragm for lithium ion battery by electrostatic spinning
CN109713203A
Diaphragm for lithium battery and preparation method thereof
CN110364665A
Meta-aramid diaphragm and preparation method thereof
CN111668425A